Il filosofo e la città (Itinera, 2012)
If the few sources at our disposal on the life and the works of Hypatia of Alexandria leave many unanswered questions about her role on the history of philosophy, her death, brought about a Christian mob, gives space to some possible analogies between the Alexandrine philosopher and Socrates, timeless paradigm of injustice against the wise. This paper, following Leo Strauss’s analyses on classical political philosophy, aims at inquiring this suggestion to reveal the hard, if not impossible, relationship between philosophy, place of an anarchist and irreligious search, and the city, place of an endless struggle between different traditions.